Pengaruh Produk Domestik Bruto, Inflasi, dan Tingkat Pengangguran terhadap Non-Performing Financing pada BUS di Indonesia dengan Metode ARDL - Devi, Sita; Juniwati, Endang Hatma (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This research explains the relationship between GDP, inflation, and unemployment rates to non-performing financing in Islamic commercial banks in Indonesia. This research uses secondary data in the form of quarterly time series from 2013 to 2022. The research data from OJK website and using a descriptive quantitative method. The data analysis method used autoregressive distributed lag (ARDL) to determine the relationship between independent to dependent variables, or the short and long term. The research results show that the long term all variables have no effect on non-performing financing partially, but in the short-term GDP and the unemployment rate has a positive effect on non-performing financing. Inflation has a negative effect on non-performing financing. However, simultaneously GDP, inflation, and the unemployment rate have a significant effect on non-performing financing.